1962
DOI: 10.1161/01.cir.26.3.379
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Serum Lipids in Relation to Emotional Stress during Rigid Control of Diet and Exercise

Abstract: In an earlier study of ambulatory humans, significant increases in the serum concentration of lipids and cholesterol were observed to correlate with emotionally stressful events in the life situation.' Other workers have also observed such changes.2-8 The changes seemed to occur independently of diet and exercise, but since it was not possible in ambulatory subjects to rule out such influences, the present study was undertaken while subjects were hospitalized, and with careful attention to maintaining diet and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
12
0

Year Published

1966
1966
1993
1993

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(14 citation statements)
references
References 7 publications
2
12
0
Order By: Relevance
“…Technical factors seem unlikely to be responsible. Watkin et al (1954) andWolf et al (1962) observed variations in serum cholesterol of the same order as found in the present study in some in-patient subjects maintained under controlled conditions of diet and exercise; Wolf et al (1962) attributed the variations to emotional environmental stress. The significant changes in serum lipids noted in the present study probably represent similar biological variations unrelated to the experimental diet under test.…”
Section: Serum Lipidssupporting
confidence: 84%
“…Technical factors seem unlikely to be responsible. Watkin et al (1954) andWolf et al (1962) observed variations in serum cholesterol of the same order as found in the present study in some in-patient subjects maintained under controlled conditions of diet and exercise; Wolf et al (1962) attributed the variations to emotional environmental stress. The significant changes in serum lipids noted in the present study probably represent similar biological variations unrelated to the experimental diet under test.…”
Section: Serum Lipidssupporting
confidence: 84%
“…Reprinted with permission of the publisher.) (32). Whenever the patients recorded feelings of stress, such as during conflicts with their doctors or roommates, both cholesterol and triglyceride levels increased (Fig.…”
Section: Stressful Life Eventsmentioning
confidence: 98%
“…Others reported that following a stress interview, free fatty acids increased as much as 159% (23,25,34). Wolf et al found that, at 1 hr after a stress interview, cholesterol increased by 70 mg/dl (32).…”
Section: Filmsmentioning
confidence: 99%
See 1 more Smart Citation
“…absence of any baseline level of cholesterol concentration, man's serum cholesterol level for any given period in his life has been found to be related to certain psychologic moods and feelings (2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16). For example, it has been shown that depressed mental patients demonstrate elevated serum cholesterol levels (4,5).…”
mentioning
confidence: 99%